2012
DOI: 10.1002/wsb.98
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting conception date variation in white‐tailed deer

Abstract: Understanding the factors that influence timing of reproduction can be of value to wildlife managers. We used estimated breeding dates of captive individual white‐tailed deer (Odocoileus virginianus) in Texas and Mississippi, USA, and wild deer populations in Mississippi, to document natural variation within individuals and populations, and to determine whether body condition, age, or moon phase explained conception date variation. Mean conception date of captive individual deer was 1 December with a median of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…climate) that trigger or cue breeding phenology remains elusive, especially at extreme latitudes or in dry environments (Aung et al 2001;Stokkan et al 2007;Bronson 2009;Dye et al 2012). Similarly, individual or population features related, for instance, to body mass, age, density or sex ratio have also been reported to be important in driving reproduction dates (Taber 1953;Mitchell & Lincoln 1973;Guinness et al 1978;Clutton-Brock et al 1983;Noyes et al 2002;Cook et al 2004;Holand et al 2004;Langvatn et al 2004;Dye et al 2012;Plard et al 2014a). However, we still lack a more integrative approach that accounts for all climatic, population and individual traits which could help disentangle the relative importance of each in driving reproduction phenology.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…climate) that trigger or cue breeding phenology remains elusive, especially at extreme latitudes or in dry environments (Aung et al 2001;Stokkan et al 2007;Bronson 2009;Dye et al 2012). Similarly, individual or population features related, for instance, to body mass, age, density or sex ratio have also been reported to be important in driving reproduction dates (Taber 1953;Mitchell & Lincoln 1973;Guinness et al 1978;Clutton-Brock et al 1983;Noyes et al 2002;Cook et al 2004;Holand et al 2004;Langvatn et al 2004;Dye et al 2012;Plard et al 2014a). However, we still lack a more integrative approach that accounts for all climatic, population and individual traits which could help disentangle the relative importance of each in driving reproduction phenology.…”
Section: Introductionmentioning
confidence: 99%
“…In the temperate zone, red deer mating is rigidly controlled by photoperiod, which has been considered the principal factor influencing the timing of the rutting season (Jaczewski 1954;Lincoln 1998;Asher et al 2011). In Mediterranean areas, it has been manifested in the popular literature that the onset of the deer breeding season is triggered, apart from the photoperiod, by environmental cues, such as the moon phase (although the theory has been repeatedly rejected; Moe et al 2007;Dye et al 2012) or the beginning of autumn rains, which to the extent of our knowledge, has not yet been scientifically tested on red deer (but see Fisher & Johnstone 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Much of the current theory about seasonal breeding is contingent on maternal condition and photoperiod [ 6 , 18 20 ]. Maternal condition is controlled by a number of factors including social rank [ 21 ], age [ 22 ], previous breeding experience [ 23 ], individual variation [ 24 26 ], and nutrition [ 27 29 ]. Litter type (i.e., litter size and sexual composition) also has been shown to affect length of gestation and timing of parturition.…”
Section: Introductionmentioning
confidence: 99%
“…In the South, daytime activity peaks at breeding in association with a particular full moon that varies by region (Alsheimer ). However, Dye et al () found no relationship with moon phase and conception date in captive and wild deer in Mississippi, USA. We also found no relationship with moon phase and DVCs overall or during the rut.…”
Section: Discussionmentioning
confidence: 99%
“…There have been conflicting reports about the effects of moon phase on deer behavior (Buss and Harbert , Zagata and Haugen , Alsheimer , Kjær et al , Dye et al ). We assumed that DVCs are associated with increased deer movement and therefore represent changes in behavior.…”
Section: Discussionmentioning
confidence: 99%